Accelerating the production of bio-oil from hydrothermal liquefaction of microalgae via recycled biochar-supported catalysts. Issue 4 (August 2021) - Kandasamy, Sabariswaran; Devarayan, Kesavan; Bhuvanendran, Narayanamoorthy; Zhang, Bo; He, Zhixia; Narayanan, Mathiyazhagan; Mathimani, Thangavel; Ravichandran, Sabarinathan; Pugazhendhi, Arivalagan
Abstract: As a highly effective nanocomposite for hydrothermal liquefaction (HTL) of microalgae, the recycled biochar synthesized from Spirulina platensis and impregnated into CeO2 has been demonstrated. The order of in situ > ex situ > biochar nanocomposites for higher bio-oil. The highest bio-oil conversion of 33% was achieved at the optimum temperature of 250 °C. The use of the biochar nanocomposite also resulted in a decrease in the oxygen and nitrogen content of the bio-oil and an increase in its heating value, which was found to be high at 35.64 MJ/kg. With the inclusion of the in situ biochar nanocomposite, energy recovery was increased by up to 65.34%. The current study has shown that low biochar nanocomposite concentrations (0.20 g), low temperature (250 °C), and short residence time (30 min) are essential for improved bio-oil yield and quality of bio-oil. Graphical Abstract: ga1 Highlights: The optimum HTL conditions were determined by RSM. Highest conversion of bio-oil yield order found as in-situ > ex-situ > biochar. For in-situ catalytic HTL, the content of nitrogen and oxygen was found to be reduced. The rate of energy recovery increased significantly through the in-situ catalytic HTL. Biochar based catalysts were eco-friendly and economic.